DETEKSI FINANCIAL STATEMENT FRAUD DENGAN ANALISIS FRAUD TRIANGLE PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BEI - KUSUMAWARDHANI, PRISCA (Jurnal Akuntansi AKUNESA, 2013)
Cases of fraud often occur in the banking sector. Because of that, this study examinesfactors of fraud triangle in detection of financial statement fraud. The independent variablesof the fraud triangle are financial stability, personal financial need that proxy, and ineffectivemonitoring and dependent variable is financial statement fraud. The population of this studyis the banking companies listed in Indonesia Stock Exchange in 2011. Data analysis wasperformed with the classical assumption and hypothesis testing using linear regression. Theresults of this study indicate that the financial stability and ineffective monitoring influencethe financial statement fraud. Meanwhile, the personal financial need has no significantimpact on financial statement fraud.Keywords: financial statement fraud, financial stability, personal financial need, ineffectivemonitoringPENDAHULUAN